The Legal Framework for the Protection of Witnesses and Whistleblowers in Algerian Legislation - Charron, Hassina; Guaffaf, Fatima (Journal of Legal Studies and Researches, 2017)
The new amendements in the code of criminal procédure for the protection of witnesses and informants who were refusing to testify or report various crimes for lack of adequate legal provisions ensure full protection after testifying or reporting. This was the modifications touched the code of criminal procedure in Algerian legislation a legal system developed for the protection of witnesses and informants in order to fill the legal vacuum that prevailed, to induce rapid report crimes and testify when required.